Are routine jobs moving south? Evidence from changes in the occupational structure of employment in the USA and Mexico - Guido Matias Cortes; Diego M. Morris (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The decline of employment in middle-wage, routine task intensive jobs has been well documented for the USA. Increased offshoring towards lower-income countries such as Mexico has been proposed as a potential driver of this decline. Our analysis provides a unique and new approach to address the question of whether trade and offshoring have impacted the occupational structure of employment in the USA by comparing the evolution of employment across 175 detailed occupational categories in both countries. We find that, with few exceptions, the occupations that have declined in the USA have also declined in Mexico. Industries with larger growth in imports from Mexico do not experience a decline in their routine employment share in the USA, nor do US industries that increase their use of Mexican intermediate inputs. There is therefore little evidence that US middle-wage jobs are moving south. The evidence is consistent with common shocks being primarily responsible for the decline of middle-wage jobs in both countries.
Keywords: J21; F66; O33; 330; employment structure; routine employment; trade; offshoring; Mexico